ASPECTS OF SUSTAINABLE DEVELOPMENT IN THE RURAL AREA. CASE STUDY - Andrei Radu IOVA; Daniela CREŢU; Elena LASCĂR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In order to analyze the inhabitants’ perception in the rural area on aspects of sustainable development, starting from the realities of the socio-economical and technical-urban analysis of the rural area in Călăraşi county, 3 specific research methods were used: the dynami, deductive and quantitative economic analysis; SWOT analysis; the economic survey or participatory research involves collecting information from the territory using as research techniques “the questionnaire” and “the interview”. The research recorded the population opinions and attitudes in 10 communes of Călăraşi county, regarding: the respondents awareness on the concept of sustainable development; cleanliness and care of the communes; prioritization of urgent investments in the studied area; the perception of changes and development potential of the area; assessing the social position of the respondents family; assessments on the quality of life in the rural area. The questionnaire, containing 13 questions, was applied on a total of 595 respondents from the 10 communes included in the study. The starting point in elaborating the questionnaire was the analysis of the social, economic and institutional situations which led to the identification of the key issues facing the localities and the potential for development. All 10 communes have common points on the population interest for the development of the local business sector; the local business sector accesed funds from various sources; there is a large available workforce, and potential for the socio economic development of the communes.